Adequate Utilization of Emergency Services in Germany: Is There a Differential by Migration Background? - Sauzet, Odile; David, Matthias; Naghavi, Baharan; Borde, Theda; Sehouli, Jalid; Razum, Oliver (Frontiers in Public Health, 2021)
Background: The role of emergency services (ES) is to provide round-the-clock acute care. In recent years, inadequate use of ES has been internationally thematised because of overcrowding and the associated cost. Evidence shows that migrant populations tend to use more ES than non-migrant but it remains to show if there is a differential in inadequacy. Method: Quantitative data from consecutive patients visiting three ES in Berlin (hospital-based outpatient clinics for internal medicine or gynecology) from July 2017 to July 2018 were obtained. Utilization was defined as adequate if the patient was admitted to hospital and/or if all of the three following criteria were fulfilled: reported to have been sent by medical staff; reported strong pain; and reported a high urgency (both ≥7, scale from 0 to 10). Differences between migrants (1st generation), their offspring (2nd generation), and non-migrants were evaluated using logistic regression. Results: Of the 2,327 patients included, 901 had a migration background. Adjusting for gender, age, gynecological hospital-based outpatient clinic, and the number of chronic diseases, 1st generation migrant patients (n = 633) had significantly lower odds than non-migrants to have an adequate utilization of services [OR 0.78, 95% confidence interval (0.62, 0.99), p-value 0.046]. For 2nd generation patients (n = 268), no statistically significant difference was found [OR 0.80, 95% confidence interval (0.56, 1.15), p-value 0.231]. Only adjusting for gynecological hospital-based outpatient clinic did weaken the association between migration status on adequacy but interactions between type of hospital-based outpatient clinic and migration were not significant. Discussion: First generation migrants show lower odds of adequate ES use compared to non-migrants. Only visiting a gynecological hospital-based outpatient clinic as opposed to internal medicine could partly explain the lower odds of adequate use among immigrants. This indicates a need for structural changes in the healthcare system: The threshold of access to general practices needs to be lowered, considering the needs of diverse subgroups of migrant patients.